The Creation of a Systematic Framework to Assess Dog Laws and Their Relationship to Societal Changes in the United Kingdom - Sarah A. Weir; Lynsey McDevitt; Clare P. Andrews; Sharon E. Kessler (Animals)
Dogs and humans have shared a complex relationship throughout history, with law serving as an important tool to manage dogs’ integration into human societies. As dogs increasingly become regarded as family members in Western countries, and as similar trends emerge globally, it is vital to understand how legislation balances the interests of stakeholders. Existing studies often focus on localised disputes and fragmented legal areas, limiting understanding of how dog-related laws interact and potentially conflict. We developed a conceptual framework to systematically analyse dog-related legislation, using the United Kingdom as a case study. Identified through a systematic search, laws were evaluated using content analysis based on the benefits provided to stakeholders, the regulated aspects of dog ownership, and whether benefits afforded to stakeholders occur in public or private spaces. We found that the greatest legislative focus was on dog welfare, dangerous dogs, and dog control, with little emphasis on areas like the breeding and sale of dogs. Eighty-two percent of laws that manage dogs in public space predominantly benefit the general public, often disadvantaging dogs and their owners, while 81% of laws that govern dogs within the home favour dogs. Owners consistently face legal obligations, but gain few benefits. These findings highlight misalignments between the law and dogs’ evolving societal roles, potentially contributing to public space conflicts and low compliance. The framework offers a tool for cross-country comparisons and assessing legislation for other species with similarly shifting roles.